Violência intrafamiliar contra a mulher: um estudo sobre a produção do cuidado na estratégia Saúde da Família - Cavalcante, Maria Michelle Bispo (2013)
Domestic violence against women gained social notoriety during the 80s, when cracks in the pact with silence that revolves around the problem started to become more and more visible. Lately, intrafamily physical assaults against female perpetrated by their intimate partners have reached a 42.2% rate of all female aggression in Brazil. Thus, to ponder about the care offered to those victims in the family health sphere – considered to be the primary door to the whole health sector – is crucial. The following study aims to understand how the production of care for female victims of domestic violence works, according to the perspective of nurses and community health workers from the Family Health Strategy in Sobral, Ceara. This is a comprehensive qualitative research with a descriptive exploratory approach that makes use of the Dialectical Hermeneutic Circle technique for data collection, as well as the Discourse Analysis for its examination. Data collection took place between September and December 2012, converging to the three Family Health Centers that most reported domestic violence cases against women in the 2009-2011 triennium. Subjects consisted of 08 nurses and 11 Community Health Workers (ACS) that for at least one year worked at these centers. All of them agreed to take voluntary part in the survey, registered through means of a Term of Consent; in accordance to Resolution 196/96 of the National Health Council and approved by the Ethics Committee from Universidade Estadual Vale do Acaraú, CAEE nº 01762512.7.0000. The results were organized into three categories, namely: special care for female victims of domestic violence; the feelings of the family health professionals toward cases of domestic violence against women; strengths and vulnerabilities of the Family Health Team in Sobral to provide care to female victims of domestic violence, underlining an extreme frailty of the care offered to female victims of domestic violence in the subject perspective, as fundamental actions to its effectiveness such as: host monitoring, qualified listening, professional guidance and support to the victims are neglected as a result of a disorganized service and its massive demand, inefficiency of the Networks for Health Care, insufficient qualification from the professionals to deal with the problematic, lack of a flowchart to better conduct the cases, under-reporting, constant feelings of loneliness and helplessness from the professionals involved , misinterpretation of the role that health care plays to better assist in violent events, lack of support from the local administration, frailty of the judiciary system and women's passive stance against the violent event are the main barriers to a better care production. We strongly emphasize that, although the Family Health Strategy in Sobral has numerous intra and inter sectoral partnerships, multidisciplinary teams, empathy and interest from some professionals working with the problem and medical resources for the treatment of physical injuries, there is still a long path to thread on in order to reach a longitudinal care for female victims of domestic violence – one that converges with the National Policy Against Female Violence.